Race woman : the lives of Shirley Graham Du Bois - Horne, Gerald (New York University Press, 2000)
"A woman of many talents, Graham Du Bois was a controversial figure who at various times championed the civil rights movement in America, the liberation struggles in Africa and the socialist development of Maoist China. Politically and culturally active long before she married W.E.B. Du Bois, Graham Du Bois wore many hats and lived many lives. Horne tells her remarkable story, exploring her work as a Harlem Renaissance playwright, biographer, composer, teacher, novelist, Left political activist, advisor and inspiration."--Jacket